Sustainable nanocarbons via biocatalysis of C-F bond cleavage by electroactive bacteria - Colavita, Paula; Costa de Oliveira, Maida (My University, 2026)
Fluorographite is a promising starting material for the synthesis of graphene and graphene oxides via top-down exfoliation routes. C-F bonds in fluorographite can be chemically substituted to form graphene oxides with tuned surface chemistry. However, most defluorination routes reported proceed via fluorographene exfoliation from fluorographite followed by refluxing in organic solvents. Herein a one-pot, biogenic and aqueous route to graphene oxide nanomaterials directly from fluorographite with no pre-exfoliation step is demonstrated. Fluorographite incubation with the electroactive bacterial species Geobacter sulfurreducens yields water-dispersible graphene oxide quantum dots and partially-defluorinated graphene oxides as the main nanomaterial products in a single step. Biocatalysis at ambient temperature and pH proceeds through direct surface contact with bacteria through C-F bond cleavage, with fluorographite serving as the sole electron acceptor for exo-electrogenic respiration. This bioexfoliation strategy presents a sustainable and green synthetic route to functionalised carbon nanomaterials with tuneable size and surface properties under ambient conditions.
PUBLISHED
Keywords: electroactive bacteria; biocatalysis; nanocarbons; bioexfoliation; fluorographene; Nanoscience & Materials; Electrochemistry; MATERIALS SCIENCE; Nanotechnology